Returning Responsibility to the Home: Outcomes of Background Checks on Low and High Achievers in Middle Basic Mathematics in North Bank Suburb - Abah J.A.; Age T.J.; Okoronkwo M.O. (Journal on Efficiency and Responsibility in Education and Science, 2018)
N/a
KerkoCite.ItemAlsoKnownAs: 10.7160/eriesj.2018.110202 4893635:M6RFB2F4 5168324:FBZEQ95G
Keywords: Household factors associated with student learning; Mathematics education; Primary education; _C:Nigeria; _authorsString:Second; A.B.; _checkedWith:AERD; _research:Quantitative; _type:Peer-reviewed article